1995
DOI: 10.1111/1523-1747.ep12613446
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Production by Cultured Human Keratinocytes: Regulation by Ultraviolet B and Ultraviolet A1 Radiation

Abstract: Keratinocytes are the primary cellular target for ultraviolet radiation in human skin, and ultraviolet radiation-induced therapeutical effects may thus be mediated by keratinocyte-derived, antiinflammatory mediators. Interleukin-10 is capable of exerting antiinflammatory effects by virtue of its capacity to suppress the production of interferon-gamma. The present study therefore assessed the ability of cultured human keratinocytes to produce interleukin-10 following ultraviolet irradiation. Exposure of long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
5
3

Year Published

1997
1997
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(116 citation statements)
references
References 15 publications
5
102
5
3
Order By: Relevance
“…Given the facts that (i) the increase and peak of the IL-10 mRNA signal correlates with the appearance of the macrophages in the epidermis, (ii) these macrophages are potent producers of IL-10, and (iii) the purity of the magnetic bead-selected NHK suspension was stated to be > 90% (not 100%), it is tempting to believe that the IL-10 mRNA detected by Kang et al [43] must be macrophage-derived. In contrast to our negative results, Grewe et al [38] and Enk et al [44] detected IL-10 mRNA in long-term cultures of NHK and in five out of nine blister roofs from non-irradiated skin by RT-PCR analysis. Comparison of their experimental set-up with ours revealed that in essence we all used the same culture conditions, but that the RT-PCR performance and visualization of the PCR products were different.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Given the facts that (i) the increase and peak of the IL-10 mRNA signal correlates with the appearance of the macrophages in the epidermis, (ii) these macrophages are potent producers of IL-10, and (iii) the purity of the magnetic bead-selected NHK suspension was stated to be > 90% (not 100%), it is tempting to believe that the IL-10 mRNA detected by Kang et al [43] must be macrophage-derived. In contrast to our negative results, Grewe et al [38] and Enk et al [44] detected IL-10 mRNA in long-term cultures of NHK and in five out of nine blister roofs from non-irradiated skin by RT-PCR analysis. Comparison of their experimental set-up with ours revealed that in essence we all used the same culture conditions, but that the RT-PCR performance and visualization of the PCR products were different.…”
Section: Discussioncontrasting
confidence: 99%
“…To our surprise, four independent research groups recently reported that NHK were able to express IL-10 mRNA and protein [38,[41][42][43][44]. Although at first sight these reports appear to disagree with our findings, we can nevertheless explain how the results in these reports and our data fit together.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations